Jonas, M. y Yacek, D. (2024). Al borde del asiento: lo que hacen los mejores profesores para implicar e inspirar a sus alumnos - Camean Ariza, Josemaría (UNIR, 2026)
Reseña
Jonas, M. & Yacek, D. (2024). On the edge of their seats: What the best teachers do to engage and inspire their students
Book review
Keywords: reseña